PENGARUH PENGALAMAN, ETIK PROFESI, OBJEKTIFITAS DAN TIME DEADLINE PRESSURE TERHADAP KUALITAS AUDIT - Syahmina, Fildzah; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to analyze the influence of experience, profession ethic, objectivity and time deadline pressure to the audit quality. In this research, the researcher is studies about audit quality at Public Accountant Firm (KAP) in Surabaya city by using independent variables i.e.: experience, profession ethic, objectivity and time deadline pressure.The population of this research are all auditors who have been works at 10 KAP in Surabaya city. The sample collection has been done by using primary data in the form of questionnaire and the data analysis technique has been done by using multiple regressions analysis technique. The data is processed in this research with the consideration that the respondents have positions i.e. junior auditor, senior auditor, and partner at least they have 2 years working experience. The result of hypothesis test in this research shows that experience, profession ethic, objectivity and time deadline pressure have significant and positive influence to the audit quality. Simultaneously all of independent variables have significant and positive influence to the audit quality. The researcher of this research recommends that in the future to increase more variables and expand the population.Keywords: Experience, Profession Ethic, Objectivity, Time Deadline Pressure, Audit Quality